PERLINDUNGAN HUKUM BAGI TANAH ULAYAT MASYARAKAT ADAT KESULTANAN DELI AKIBAT NASIONALISASI NV DELI MAATSCHAPPIJ [Legal Protection of the Communal Land Rights of the Deli Sultanate due to the Nationalization of NV Deli Maatschaapij] - Jeremy Aidianto Naibaho; Bambang Daru Nugroho; Yusuf Saepul Zamil (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2020)
AbstractNationalization of a Dutch-owned plantation company, NV Deli Maatschappij, was an attempt by the government to improve national economic situation. However, during the process, communal land which was concessioned to the plantation, was also nationalized and not given compensation by the government which resulted the indigenous people of Deli Sultanate losing their customary land. The former plantation land was converted to Cultivation Rights and handed over to the State Plantation Company This problem led to a prolonged conflict over ownership of the former estate. The purpose of this study is to determine the validity of the nationalization process carried out by Indonesian government on the existence of indigenous peoples’ customary land rights and obtain settlement of customary land rights of indigenous peoples as the impact on nationalization. Furthermore, this research is normative legal research (library research) with a statutory approach (statue approach).Keywords: Nationalization, Communal Land, CompensationAbstrakProses nasionalisasi Perusahaan Perkebunan milik Belanda, yaitu NV Deli Maatschappij adalah upaya pemerintah untuk memperbaiki perekonomian Negara. Namun dalam pelaksanaannya tanah ulayat yang dikonsesikan kepada perkebunan juga ikut ternasionalisasi dan tidak diberikan ganti kerugian oleh pemerintah yang berakibat Masyarakat Adat Kesultanan Deli kehilangan tanah ulayatnya. Tanah bekas perkebunan diubah menjadi Hak Guna Usaha dan diserahkan kepada Perusahaan Perkebunan Negara. Hal ini menimbulkankonflik berkepanjangan tentang kepemilikan tanah bekas perkebunan tersebut. Penelitian ini merupakan penelitian hukum normatif (library research) dengan pendekatan undang-undang (statue approach). Tujuan penelitian ini adalah untuk menilai keabsahan proses nasionalisasi yang dilakukan oleh pemerintah Indonesia terhadap eksistensi hak ulayat Masyarakat Adat dan memperoleh penyelesaian sengketa tanah ulayat Masyarakat Adat sebagai dampak atasnasionalisasi.Kata Kunci: Nasionalisasi, Tanah Ulayat, Ganti Rugi